The Problematic of Disaster Management Law and Policy in Nigeria: A Study of Bayelsa State - Amede, Ogochukwu Harrison; Ejumudo, Kelly Bryan Ovie (Universitas Negeri Semarang, 2021)
The study examined the problem of disaster management in Nigeria using Bayelsa State as a case study. Four null hypotheses were raised and tested at a 0.05 level of significance. The study adopted the descriptive survey design and sample sizes of 300 adults were drawn from fifteen (15) affected communities in Bayelsa State. The instrument used for data collection was a disaster management questionnaire and the data were analyzed using chi-square. The finding of the study revealed that there is a significant relationship between poor integrated policy and action plan as well as weak institutional capacity and collaboration of disaster management agencies and effectiveness of disaster management in Bayelsa State. The study clearly showed that there is a significant relationship between poor commitment and piece-meal approach by the multi-layered levels of government as well as poor stakeholders’ participation and synergy and effectiveness of disaster management in Bayelsa State. The study recommended among others that long-term monitoring and surveillance mechanism; continuous provision of infrastructure for the host communities by prospecting oil companies; adequate funding by governmental and non-governmental and the development of a national oil spill contingency plan should be adopted and deployed with an eye to guaranteeing sustainable development of the environment in the region.